How Christiana Learned Her Catechism: Catechisms, Family Religion, and Lay Literacy in Seventeenth-Century England. (25th October 2018) - McQuade, Paula
Abstract: Multiple accounts confirm the importance of domestic catechesis to early modern women and men's reading and writing practices, but we know far less than we would like about the practice of catechesis within the godly home. This article seeks to recreate, as much as possible, how seventeenth-century laymen and women used print catechisms. It does so first by examining the multiple manuals written by godly ministers designed to help the godly householder with domestic catechesis. These ministerial manuals urged householders to recognize when a child didn't fully understand a doctrine and to elaborate upon it when he did. They taught critical thinking skills to laymen and women, using features such as superscript numbers and letters and italicization to reinforce their instruction. The article compares these ministerial accounts with two manuscript catechisms composed within print catechisms. Likely written by laymen or women, these works suggest that their authors had to some degree internalized ministerial advice, as they rewrite questions or insert elaborate question and answer sequences to extend the instruction of the print text. In one case, a user even interleaved a print catechism with an original manuscript catechism, changing the format of the printed book to serve better domestic religion instruction. These composite catechisms, I argue, provide a textual representation of the dialogic processes of the transmission of knowledge. Far from passive, solitary readers, these users actively remade books as they used them. Catechesis provided laymen and women with the doctrinal knowledge and analytic and textual skills foundational to authorship.